UNIVERSITY STUDENTS URGED TO EQUIP THEMSELVES WITH KNOWLEDGE - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, May 2015 University students were urged to equip themselves with various knowledge and skills to face the challenges posed by globalisation and to increase their capabilities in dealing with these challenges.